Bacterial proteins pinpoint a single eukaryotic root - Derelle, Romain; Torruella, Guifré; Klimeš, Vladimír; Brinkmann, Henner; Kim, Eunsoo; Vlček, Čestmír; Lang, B Franz; Eliáš, Marek (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The large phylogenetic distance separating eukaryotic genes and their archaeal orthologs has prevented identification of the position of the eukaryotic root in phylogenomic studies. Recently, an innovative approach has been proposed to circumvent this issue: the use as phylogenetic markers of proteins that have been transferred from bacterial donor sources to eukaryotes, after their emergence from Archaea. Using this approach, two recent independent studies have built phylogenomic datasets based on bacterial sequences, leading to different predictions of the eukaryotic root. Taking advantage of additional genome sequences from the jakobid Andalucia godoyi and the two known malawimonad species (Malawimonas jakobiformis and Malawimonas californiana), we reanalyzed these two phylogenomic datasets. We show that both datasets pinpoint the same phylogenetic position of the eukaryotic root that is between "Unikonta" and "Bikonta," with malawimonad and collodictyonid lineages on the Unikonta side of the root. Our results firmly indicate that (i) the supergroup Excavata is not monophyletic and (ii) the last common ancestor of eukaryotes was a biflagellate organism. Based on our results, we propose to rename the two major eukaryotic groups Unikonta and Bikonta as Opimoda and Diphoda, respectively.
Keywords: Diphoda; bakteriální proteiny; eukaryote phylogeny; Phylogeny; datové soubory jako téma; LECA; Eukaryota; Bacteria; Opimoda; phylogenomics; Genes, Bacterial; Bacterial Proteins; fylogeneze; bakteriální geny; Datasets as Topic